KAJIAN AL-ISLAM DAN KE-MUHAMMADIYAHAN (AIK) UNIVERSITAS MUHAMMADIYAH SUMATERA BARAT DALAM PERSPEKTIF FILSAFAT ILMU KE-ISLAMAN - Riki Saputra (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
In the midst of faltering studies of al-Islam and Kemuhammadiyahan within the faculty of Muhammadiyah University of West Sumatra, it is necessary to echo a picture of the development of science in general which is very revolutionary. Changes and paradigm changes are very common, while among Islamic religious scientists it looks rather slow. That is because the paradigm that was built by a scientist was later sacred by the next generation of scientists. Consequently, something that should be profane becomes sacred, which should be open-ended to be closed, which should be the object of study being an ideology and so on. This also happened in the design of Al-Islam and Kemuhammadiyahan studies. For the further development of the AIK study, the question remains needed is whether the new paradigm to be offered later is then followed by changes to the next paradigms or re-stuck to the stagnation of science. Researchers try to apply the theory of Soroush and Lakatos about the development of science in Al-Islam and Kemuhammadiyahan. This research certainly hopes will arouse the scientific community, especially AIK so that it does not become a closed science, but is open and integrative with other sciences. Keywords: Al-Islam and Muhammadiyahan, Philosophy of Science-Islam